Early Re-Bleed in Patients with Fundal Varices Treated with Injection Cynoacrylate (Histoacryl®) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of early re-bleed in patients with fundal varices treated with Injection Cynoacrylate (Histoacryl®).Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at the Department of Gastroenterology-Hepatology, Shaikh Zayed Hospital, Lahore from April 2012 to October 2012.Materials and Methods: 100 patients were recruited. Injection Histoacryl® was injected and volume of injection was not exceeded from more than 1ml at one site. Maximum number of injection did not exceed more than two per site. After the procedure patient was shifted to Gastroenterology Ward where he or she was observed for early re bleed and data was noted regularly for 5 consecutive days.Results: Present study showed mean age of the patients was 48.4±10.8 years. Patient distribution by gender, there were 68 (68%) male and 32 (32%) female patients. Out of 100, 12% patient had early rebleed in patients with fundal varices.Conclusion: The frequency of early re-bleed in patients with fundal varices treated with Injection Cynoacrylate (Histoacryl®) is low. It is suggested that more multi-center studies should be conducted on large sample size so that the exact frequency of early rebleed could be obtained